Influência do ambiente na heterogeneidade de brotação e floração de macieiras - Pertille, Rafael Henrique (2021)
Temperate fruit trees, such as apple trees, present dormancy as one of the mainphases in their production cycle. The main characteristics of the cultivation site thatdirectly influences the entry and exit of dormancy are the quantity and quality of chill.When grown in a location with a low quantity and quality of chill, the plants showheterogeneous flowering and budding, and reduced leaf area and productivity,potentially due to decreasing formation and maintenance of floral structures. Theobjective of the work was to study the behavior of the plant, in relation to itsdormancy dynamics and the formation of floral and vegetative structures at differentaltitudes, and to study the influence of temperatures on phenological events. Thestudy was carried out in the region of Palmas – PR, at the Lovo orchard, altitude of1140 m, with the cultivars Eva, Galaxy and Fuji Suprema, and at the Horizonteorchard, altitude of 1310 m, with the cultivars Galaxy and Fuji Suprema. During theyears 2018, 2019 and 2020, the isolated node test was performed biweekly todetermine the mean time of budburst (MTB). The early flowering dates from 2012 to2020 were used to correlate with the average daily temperatures during the year,using the Partial Least Squares (PLS) methodology. In the fall of 2019 and 2020,shoots of branches marked in the previous winter were evaluated to understand thetypes of shoots that occur in each portion of the branches, for each cultivar andlocation. The dormancy dynamics of the Gala cultivar were observed to respond toenvironmental changes, through an increased depth of dormancy and a greaterspeed of entry and exit of dormancy, in a location with cooler and morehomogeneous temperature conditions. Deep endodormancy was not observed inEva, unlike the cultivars Gala and Fuji. The early flowering date is controlled by bothtemperature during the chilling phase and the forcing phase. The production ofbranches and lateral spurs was higher in the Horizonte orchard, with a better chillaccumulation, however the plants of Lovo orchard, which had less chill accumulation,had a higher total number of spurs, due to compensation for low lateral sproutingthrough the formation of bourse-over-bourse structures, which maintained theproductive potential. In addition, the plants in the Horizonte orchard formed longerbranches than those in the Lovo orchard.